Unemployment Experts: Governing the Job Search in the New Economy. Issue 4 (November 2021) - Sheehan, Patrick
In recent years, sociologists have examined unemployment and job searching as important arenas in which workers are socialized to accept the terms of an increasingly precarious economy. While noting the importance of expert knowledge in manufacturing the consent of workers, research has largely overlooked the experts themselves that produce such knowledge. Who are these experts and what kinds of advice do they give? Drawing on interviews and ethnographic fieldwork conducted at three job search clubs, the author develops a three-fold typology of "unemployment experts": Job Coaches present a technical diagnosis that centers mastery of job-hunting techniques; Self-help Gurus present a moral diagnosis focused on the job seeker's attitude; and Skill-certifiers present a human capital diagnosis revolving around the job seeker's productive capacities. By offering alternative diagnoses and remedies for unemployment, these experts give job seekers a sense of choice in interpreting their situation and acting in the labor market. However, the multiple discourses ultimately help to secure consent to precarious labor markets by drawing attention to a range of individual deficiencies within workers while obfuscating structural and relational explanations of unemployment. The author also finds that many unemployment experts themselves faced dislocations from professional careers and are making creative claims to expertise. By focusing on experts and their varied messages, this paper reveals how the victims of precarious work inadvertently help to legitimate the new employment regime.